1979
DOI: 10.1088/0031-9155/24/5/006
|View full text |Cite
|
Sign up to set email alerts
|

Solar dosimetry of the face: the relationship of natural ultraviolet radiation exposure to basal cell carcinoma localisation

Abstract: Measurements have been made of the distribution of natural ultraviolet radiation (UVR) at 41 sites on the face of a large fibreglass model of a head. The dosemeter used was the polymer film polysulphone. The results have been correlated with published values of the distribution of basal cell carcinomas on the face. Although the comparison has highlighted the problems of trying to relate frequency of skin tumour occurrence to sunlight exposure, the present results are compatible with the hypotheses that human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 13 publications
3
61
0
Order By: Relevance
“…The correlation between facial BCC tumour density 14 and UV exposure examined by Diffey et al 13 did not show a strong relationship. This was partly due to differences in latitude between the two locations in which the data sets were collected.…”
Section: Comparisons With Facial Bcc and Sk Site Incidence To Uv Expomentioning
confidence: 78%
See 2 more Smart Citations
“…The correlation between facial BCC tumour density 14 and UV exposure examined by Diffey et al 13 did not show a strong relationship. This was partly due to differences in latitude between the two locations in which the data sets were collected.…”
Section: Comparisons With Facial Bcc and Sk Site Incidence To Uv Expomentioning
confidence: 78%
“…Detailed facial site UV exposures measured in this study were further compared to histologically confirmed BCC incidences recorded by Brodkin 14 as detailed by the exposure comparison of Diffey et al 13 . This data set, excluding superficial type BCC were diagnosed in the Oncology Section of the Skin and Cancer Unit, University Hospital, New York, and may therefore differ in BCC distribution observed in an Australian population for which the ambient UV environment is likely to be different to that which subjects diagnosed in the Brodkin et al 14 study were exposed.…”
Section: Incidence Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, bias due to a selected sample of the Nambour population being followed is unlikely, since there were no significant differences between participants in the follow-up study and non-participants with respect to any identified risk factors. Only solar lentigines occurred more frequently in par- (Urbach, 1969;Diffey et al, 1979). (Detailed site-distribution data were not gathered in our follow-up study.)…”
Section: Carcinoma (Scc) In Relation To Hair Colour Number Of Painfumentioning
confidence: 90%
“…Clinically BCC appears as a slowly expanding locally malignant neoplasm with ultraviolet light as its major cause (Di ey et al, 1979;Gallagher et al, 1995;Kricker et al, 1994). A rare familiar form, the basal cell nevus syndrome (BCNS), exists in which patients develop multiple BCC:s at early age.…”
Section: Introductionmentioning
confidence: 99%